Pengaruh Motivasi dan Lingkungan Studi Mahasiswa Terhadap Minat Menjadi Akuntan Publik Pada Mahasiswa Program Studi Akuntansi UMBY - Kuingo, Rendy Maychell; Astuti, Tutut Dewi (Universitas Pahlawan Tuanku Tambusai, 2024)
The Objective of this research is to know the influence of: (1) The motivation of Accounting students of Faculty of Economics of UMBY towards their interest to be a public accountant, (2) The Study Environment of students of Faculty of Economics of UMBY towards their interest to be a public accountant. This research belongs to survey research. The population of this research is 208 Accounting students of the Faculty of Economics of Mercubuana Yogyakarta University who have taken Auditing 1 subject and the sample of this research is the 140 respondents among them. The purposive sampling technique was employed to obtain the sample of the research. The data of this research was obtained through questionnaires. Analysis Prerequisite Test of this research consisted of normality test, linearity test, multicolinearity test, and heteroscedasticity test. Simple linear regression and multiple linear regression technique were employed as the data analysis technique.